Feeding Patterns of Mosquitoes (Diptera: Culicidae) in the Atlantic Forest, Rio de Janeiro, Brazil. Issue 5 (11th July 2015) - Alencar, Jeronimo; Mello, Cecília Ferreira de; Gil-Santana, Hélcio R.; Giupponi, Alessandro Ponce de Leão; Araújo, Andressa Nunes; Lorosa, Elias Seixas; Guimarães, Anthony Érico; Silva, Júlia dos Santos
Abstract : The stomach contents of culicids from the Atlantic Forest in Rio de Janeiro state, Brazil, were analyzed using the precipitin technique to evaluate the feeding patterns of the species. Sampling was performed from February 2012 to December 2013, using CO2 -baited Centers for Disease Control and Prevention traps to catch mosquitoes from 15 00 to 07 00 hours. The following antisera were used: bird, rodent, opossum, human, horse, capybara, lizard, and frog. Of the 325 adult bloodfed females caught and analyzed, 273 (84.0%) reacted in the precipitin test. The percentage of specimens with a positive reaction to a single antiserum included bird (39.2%), rodent (22.5%), opossum (13.2%), capybara (6.6%), horse (5.7%), frog (6.2%), human (4.0%), and lizard (2.6%). The specimens that reacted positively against more than one blood source (46) most frequently presented the following combinations: bird + rodent and bird + frog (17.4%), followed by bird + human (13.0%). The predominance of positive results for birds suggested that the avian-rich environment might have influenced the feeding behavior of the culicids.